Sub-toxic zinc oxide nanoparticles modulate PSD-95 and shank 3 protein levels - Castro, Ana Carolina Fernandes Vieira de (2019)
The effect of zinc on neuronal systems is growing interest in scientific research due to a possible role as a modulator of synaptic activity. Additionally, recent research points to the therapeutic potential of zinc oxide nanoparticles (ZnO NPs) on neuronal cells. These nanoparticles are excellent drug carriers to the brain because, besides having positive characteristics for the protection of cellular homeostasis, they are small, allowing them to pass the blood brain barrier and interact directly within these cells. In this sense, the present thesis explored the effect of sub-toxic ZnO NP concentrations on cell viability and ROS production in SH-SY5Y cells, as well as their impact on the expression levels of PSD-95, SHANK 3 and β-actin proteins. The results showed increases in PSD-95 and SHANK 3 protein expression without variations in β-actin expression after neuronal cell exposure to sub-toxic concentrations and at reduced exposure times to ZnO NPs. Future efforts should be implemented to investigate how this increase may reduce brain impairment associated with neurodegenerative diseases. However, the results here presented have clearly identified some of the synaptic molecular targets of ZnO NPs and that these NPs are worthwhile exploring for their therapeutic potential.